Red-teaming as a research validation method for systems engineering thesis students - Ferris, Timothy L. J.; Camelia, Fanny; Mattsson, Tuomas; Machado, Rogério C. (Wiley, 2022)
All research projects need a forward path method for performing the investigation, making findings and reaching conclusions. In addition, project methodology must include methods that test the truth of the knowledge claimed to have been developed through the project. We address the specific issue of validation in thesis projects in systems engineering (SE) programs where the intended outcome is either an application of SE method or an investigation of a topic in SE. We present red-teaming (RTing) as a validation method for results of SE research. We discuss two case studies of thesis projects which used a RTing method to evaluate a proposed method for doing something. From this we discuss the strengths and weaknesses of the RTing method in thesis projects and provide guidelines for use of RTing as a project outcomes evaluation method. We conclude RTing is a useful method to evaluate a thesis project which generates a design or a method because it uses a method not directly influenced by the student’s assumptions in the design of the project. The RTing method is constrained by the challenges of finding willing red-team (RT) members, project schedule, and the RT member’s knowledge of the subject.